Applying a dyadic outcomes approach to supporting older carers and care‐recipients: A qualitative study of social care professionals in England. (20th July 2022) - Rand, Stacey; Zhang, Wenjing; Collins, Grace; Silarova, Barbora; Milne, Alisoun
Abstract: There are an estimated 2 million older carers, aged 65 or over, in the UK. Older carers are more likely to care for a co‐resident spouse/partner, provide high‐intensity support and have their own health problems. The literature suggests that a 'dyadic outcomes approach' to social care (i.e. services and support that seek to understand and improve the quality of life of the older carer and the person they support, individually and together) may be especially beneficial for older carers. Such an approach may be applied in needs assessment and review, service evaluation, planning and delivery, or commissioning. However, there is a paucity of evidence of its effectiveness and feasibility in practice. In this qualitative study, we explored views of social care professionals in England on supporting older carers, as well as the feasibility, potential benefits and challenges of applying a dyadic outcomes approach into policy and practice. Overall, 25 professionals were interviewed between January and July 2021, including social workers, team leads, managers, commissioners and other representatives from local authorities, care providers and carer organisations. Findings indicate that there is limited focus on the specific needs of older carers in practice. Participants recognised the potential benefits of a dyadic approach, including the development of a holistic view that enables an effective response to supporting quality of life, for both carer and care‐recipient, and building trust when working to support the caring dyad. Barriers to applying a dyadic approach included data protection and sharing, both within and between organisations; required workforce skills, experience and knowledge; and insufficient and competition‐oriented adult social care funding that discourages collaborations between agencies. Despite the potential of the approach to improve the effectiveness of support for older caring dyads, these challenges need to be recognised and addressed if it is to be implemented.